Qualidade de carne suína. 1. efeito do gene halotano sobre a deposição de gordura intramuscular. 2. efeito da suplementação com minerais no pré-abate - Alves, Luana Ribeiro (2011)
They had been studied a total of 304 pigs, barrows and gilts, with approximately 150 days old. Initially 144 pigs were analyzed to evaluate the effect of the HAL gene on the deposition of GIM. Subsequently, we studied 160 animals in order to investigate the interference of the minerals Mg, Zn, Se and Cu, added to water pen, pre-slaughter, the final quality of pork, and for each of the mineral teste were studied a total of 140 pigs (20 treated and 20 controls) were housed in two pens of rest previously prepared, and the administration period of 12 hours of the mineral. For analysis of GIM, initially characterized the genotype of the HAL gene in animals by analyzing DNA from blood using one protocol of PCR-RFLP protocol and GIM was measured from samples collected from the semimembranosusi muscle. For the analysis of minerals were evaluated for meat quality characteristics: pH 45 minutes, pH 24 hours, meat color and WHC. There was no significant difference in allele n halothane gene in the deposition of GIM, when heterozygous. Pigs subjected to dietary water containing the mineral magnesium, as well as the mineral selenium showed higher pH 45 minutes, pH 24 hours and WHC than those who did not under go the same showing thus a higher quality of meat. In addition, meat color was more pale pigs did not have access to magnesium. There were no significant differences in the quality of meat for the animals supplemented with mineral springs containing copper and zinc.